The prevalence of electrocardiographic early repolarization in an adult cohort with chronic kidney disease and its impact upon all-cause mortality and progression to dialysis - Hajhosseiny, Reza; Rajani, Ronak; Khavandi, Kaivan; Sebag, Frédéric A.; Mashayekhi, Soudeh; Wright, Matthew; Goldsmith, David (Frontiers in Physiology, 2013)
Background Electrocardiographic early repolarisation (ER) occurring in <5% of general/atherosclerotic populations, is a marker of sudden cardiac death (SCD). The prevalence of ER in chronic kidney disease (CKD) patients, in whom SCD is common, is unknown. We aimed to determine the prevalence, contributing factors and relationship of ER to all-cause mortality and progression to dialysis in CKD patients. Methods A retrospective study of 197 patients with stage 3-5 CKD. Full demographic data were collected including cardiovascular risk factors and history. All patients underwent a 12-lead ECG, analysed for the presence of ER and other ECG findings. ER was defined as elevation of the QRS-ST junction (J point) by at least 0.1mV from baseline with slurring/notching of the QRS complex. The primary and secondary endpoints were all cause mortality and progression to dialysis respectively at one year. To control for the effects of CKD, we evaluated the ECGs of 39 healthy renal transplant donors (RTD). Results CKD patients had a mean age of 61.5 (±16.1). Prevalence of ER in pre-dialysis patients with CKD stage 4 and 5 was higher than in RTD (26.4% vs. 7.7%, p=0.02). ER frequency increased with CKD stage (stage 3: 7.7%, stage 4: 29.7% and pre-dialysis stage 5: 24.6%), but decreased in dialysis patients (13%). On multivariate analysis only the QRS duration was a significant independent predictor of ER (OR 0.97, 95% CI, 0.94-0.99, p=0.01). At one-year follow-up there were 24 (12%) deaths in the patients with CKD of whom 5 (21%) had ER. ER wasn't a predictor of all cause morality (p=1.00) and had no effects on the rate of progression to dialysis (p=0.67). Conclusions ER is more common in pre-dialysis CKD patients, compared to healthy RTD but is not associated with increased 1-year mortality or entry onto dialysis programmes. Further longitudinal studies are indicated to determine whether this increased prevalence of ER is associated with the rate of SCD seen in this population.